Neonatal outcomes of preterm infants with in-utero exposure to drugs of substance use: US national data - Subhash Puthuraya; Sreenivas Karnati; Hasan Othman; Rachana Sripathi; Vanishree Nandakumar; Hany Aly (Elsevier, 2023)
Background: Infants exposed prenatally to drugs of substance use are at increased risk for seizures, strabismus, feeding difficulty, and neurodevelopmental delays. Exposed preterm infants may have additional morbidities related to prematurity. There is limited literature on national outcomes of preterm infants exposed to drugs of substance use. We aimed to evaluate the trends and neonatal outcomes of preterm infants born in the USA who were exposed in-utero to drugs of substance use. Methods: Retrospective cohort study of preterm live born (<37 weeks gestation) exposed in-utero to opioids, hallucinogens, or cocaine in the Healthcare Cost and Utilization Project database from 2002 to 2017. Neonatal outcomes were identified using international classification of diseases 9&10 codes. Results: Of the 54,469,720 live-born infants, 7.7% (4,194,816) were preterm, and 58 679 (1.4%) were exposed in-utero to maternal opioids/hallucinogens (n = 39,335) or cocaine (n = 19,344). There was a trend for increased exposure to opioids/hallucinogens (Z score = 76.14, p < 0.001) during the study period. Exposed preterm infants had significantly more neurological anomalies, intra-ventricular hemorrhage and periventricular leukomalacia (p < 0.001). Conclusions: There was a trend for increased in-utero exposure to opioids and hallucinogens in the preterm infants in the USA. Exposed preterm infants had more neurological morbidities.